THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND FIRM PERFORMANCE IN THE SCOPE OF SUSTAINABILITY: AN ANALYSIS IN THE BIST KY INDEX (Third Sector Social Economic Review, 2022)
In this study, it is aimed to investigate whether the corporate governance rating grades, which are used as a performance indicator of the corporate governance application levels of the companies, are evaluated as an important information that will affect the future cash flows of the companies, and as a result, whether they are reflected in the stock prices. For this purpose, the case study method was used to investigate whether the stock prices of the companies listed on the BIST and included in the corporate governance index (excluding financial institutions) showed an abnormal change in the 2008-2018 period around the dates of the announcement of their corporate governance rating grades.As a result of the research, when 254 observations of 32 companies were taken into account, it was observed that there were abnormal price movements in the 20-day period before and after the announcement of the corporate governance rating of the companies. The results indicate that corporate governance ratings are considered as important information for investors, which is reflected in the price. It is observed that investors who hold shares applying corporate governance principles during the event period have an average cumulative abnormal return of 160.32%. It is observed that this situation is at the cumulative average abnormal return level of 97.62% when the day and after the event is taken into account.
Keywords: Corporate sustainability; corporate governance; firm performance; abnormal return; BIST